PriorTD: A Method for Prioritization Technical Debt - Detofeno, Thober; Malucelli, Andreia; Reinehr, Sheila (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Advances in Technical Debt (TD) have enabled the identification of numerous immature artifacts and their impacts on software maintenance and evolution. However, organizations can identify and understand the impacts of TD, but challenges arise when deciding which TD item should be paid for and which should be deferred. These decisions are influenced by many contextual factors that cannot be determined by considering source code alone. Prioritization strategies must consider the business objectives, the scope of the projects, and the needs of the development teams. This paper presents the PriorTD method, which prioritizes TD from the most relevant source code for the project and provides scenarios to meet business needs. It was built throughout two cycles of action research, over two years and eight months, in a software development company. PriorTD analyzes the source code and TD from the perspective of the importance of the source code for the project, team, and managers and provides guidance and support for all involved to understand the decisions related to the prioritization of TD.